Development of engineering material selection computer package for enhanced decision making - Nwankwo, Daniel; Okolie, Paul Chukwulozie; Madumere, Augustine Uzodinma; Okonkwo, Ugochukwu Chuka; Okoye, Chibuzo Ndubuisi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2025)
An engineering material selection computer package for enhanced decision making has been developed. MATLAB software (2021 edition) which has built-in application design environment was employed for the development. The package integrates three main windows: the Login Window, the Add Material Window, and the Select Material Window. Through a detailed review of existing material selection methodologies, this research work presents a unified software solution tailored for engineering material selection. The software automates material classification, provides systematic ranking mechanisms, and offers detailed property displays during selection. Results demonstrate successful integration of material selection into a user-friendly interface, automated classification based on predefined parameters, and systematic ranking mechanisms. The software enables seamless updates, incorporates interactive documentation, and facilitates efficient material selection. The package is recommended for use by engineering students and practicing engineers, providing them with a valuable tool for material selection processes in their respective fields. Further recommendations include, regular software updates and integration with external databases to optimize impact. Overall, this thesis presents a robust software solution that enhances efficiency and accuracy in engineering material selection, aiding decision-making processes across engineering industries.